The wisdom of finance : discovering humanity in the world of risk and return - Mihir A. Desai (Mihir Arvind), 1968- (Houghton Mifflin Harcourt, 2017)
The Harvard Business School professor draws upon literature, film, philosophy, and history to argue that, at the core of finance and financial practices, there is a place for principles, ethics, and humanity